Kajian Biodegradasi Filem Plastik Campuran Polistiren Dengan Poli (3-Hidroksibutirat) Dalam Tanah - Octaviani, Melzi; Zaini, Erizal; Djamaan, Akmal (Jurnal Farmasi Andalas, 2013)
The degradation of a plastic film containing polymer synthetic polystyrene (PS) and biopolymer poly(3-hydroxybutyrate) [P(3HB)] in soil has been carried out based on soil burial test. Result showed that the amount of P(3HB) in plastic film containing PS and P(3HB) influence the degradation rate of plastic film. Rate degradation measured use linear regression equality and parameter is indicated by the slope (k), degradation time 50% (t 50%), and degradation time 95% (t 95%). Degradation plastic film which occurred in soil with ratio PS/P(3HB) 85:15 was k = 0.90 %/week, t 50% = 55.13 weeks and t 95% = 105.29 weeks, followed by PS/P(3HB) 90:10 and PS/P(3HB) 95:15. In contrast, plastic film which made from pure PS (100:0) occurred slow with slope value (k) = 0.14 %/week, t 50% = 345.07 weeks, and t 95% = 655.63 weeks. Result of SEM test showed that damage occurred and erosion at surface of plastic film as long as observation time in various environment condition.Â